Gelatin extraction from the indigenous Pangasius catfish bone using pineapple liquid waste - Yoni Atma; Hisworo Ramdhani (Universitas Gadjah Mada, 2017)
Gelatin extraction from fish bone has traditionally involved hydrogen chloride and/or sodium hydroxide during pre-treatment. However, these chemicals have begun to be abandoned because of their associated safety and environmental issues. Several studies have looked at the use of citric acid as a safer alternative in fish bone gelatin extraction. The aim of this research was to extract gelatin from the bone of Pangasius catfish with pineapple liquid waste. The extraction was performed in two steps: pre-treatment followed by main extraction at various times (24–56 h) and temperatures (45–75°C). Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) was used as a confirmation test and showed a band for gelatin at 120 kDa. Gelatin yields were calculated as the ratio of weight of dried gelatin to the total weight of fish ossein. The results indicated that pineapple liquid waste can be used for fish bone gelatin extraction. The recommended conditions for extraction of fish bone gelatin using pineapple liquid waste are 56 h of pre-treatment and 5 h of main extraction at a temperature of 75°C. The gelatin yield was 6.12% and the protein concentration 4.00 g/100 g.